Montefalco, 1950: una iniciativa pionera para la promoción de la mujer en el ámbito rural mexicano / Montefalco, 1950: a pioneering enterprise to improve the condition of women in rural Mexico - Lucina Moreno-Valle; Mónica Meza (Studia et Documenta)
The apostolate of Opus Dei with women in rural Mexico acquired greater force through the work carried out in Montefalco, a former agricultural hacienda. This study recounts the arrival of the first members of Opus Dei to Mexico, the acquisition of the building, and the development of the first educational and spiritual activities, which would also become a farm-school for the inhabitants of the town.